The cost of a catheter: An environmental perspective on single use clean intermittent catheterization. Issue 7 (14th August 2018) - Sun, Andrew J.; Comiter, Craig V.; Elliott, Christopher S.
Abstract : Methods: We estimated the prevalence of CIC use in the United States using a neurogenic population, consisting of persons with multiple sclerosis, spina bifida, and spinal cord injury. We measured catheter samples to obtain the amount of waste per catheter. Results: At least 300 800 persons in the United States perform CIC for neurogenic bladder management. Assuming five catheterization events per day, the amount of waste generated by single‐use CIC is between 26 500 to 235 400 pounds or 22 600 to 564 000 liters per day, depending on catheter model. Conclusions: Single‐use CIC may generate up to 85 million pounds or 206 million liters of waste annually, equivalent to more than 26 000 cars or 80 Olympic‐sized swimming pools. Laid end‐to‐end, there is enough catheter length circumscribe the world more than 5.5 times. The most common materials used in catheter construction have little to no degradation once in a landfill. Given the unproven clinical benefit of single‐use catheterization, the environmental impact and alternatives should be considered.